Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Highly contaminated river otters (Lontra canadensis) are effective biomonitors of environmental pollutant exposure - Michelle Wainstein; Louisa B. Harding; Sandra M. O’Neill; Daryle T. Boyd; Fred Koontz; Bobbi Miller; Cornelya F. C. Klütsch; Philippe J. Thomas; Gina M. Ylitalo (Environmental Monitoring and Assessment, 2022)
River otters ( Lontra canadensis ) are apex predators that bioaccumulate contaminants via their diet, potentially serving as biomonitors of watershed health. They reside throughout the Green-Duwamish River, WA (USA), a watershed encompassing an extreme urbanization gradient, including a US Superfund site slated for a 17-year remediation. The objectives of this study were to document baseline contaminant levels in river otters, assess otters’ utility as top trophic-level biomonitors of contaminant exposure, and evaluate the potential for health impacts on this species. We measured a suite of contaminants of concern, lipid content, nitrogen stable isotopes (δ 15 N), and microsatellite DNA markers in 69 otter scat samples collected from twelve sites. Landcover characteristics were used to group sampling sites into industrial (Superfund site), suburban, and rural development zones. Concentrations of polychlorinated biphenyls (PCBs), polybrominated diphenyl ether flame-retardants (PBDEs), dichlorodiphenyl-trichloroethane and its metabolites (DDTs), and polycyclic aromatic hydrocarbons (PAHs) increased significantly with increasing urbanization, and were best predicted by models that included development zone, suggesting that river otters are effective biomonitors, as defined in this study. Diet also played an important role, with lipid content, δ 15 N or both included in all best models. We recommend river otter scat be included in evaluating restoration efforts in this Superfund site, and as a potentially useful monitoring tool wherever otters are found. We also report ΣPCB and ΣPAH exposures among the highest published for wild river otters, with almost 70% of samples in the Superfund site exceeding established levels of concern.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Anterior cingulate dopamine turnover and behavior change in Parkinson’s disease - Catherine L. Gallagher; Brian Bell; Matthew Palotti; Jen Oh; Bradley T. Christian; Ozioma Okonkwo; Jitka Sojkova; Laura Buyan-Dent; Robert J. Nickles; Sandra J. Harding; Charles K. Stone; Sterling C. Johnson; et al. (Brain Imaging and Behavior, 2015)

Adverse foraging conditions may impact body mass and survival of a high Arctic seabird - Ann M. A. Harding; Jorg Welcker; Harald Steen; Keith C. Hamer; Alexander S. Kitaysky; Jérôme Fort; Sandra L. Talbot; Leslie A. Cornick; Nina J. Karnovsky; Geir W. Gabrielsen; David Grémillet (Oecologia, 2011)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)